2017
DOI: 10.1016/j.sna.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze film damping and stiffening in circular CMUT with air-filled cavity: Influence of the lateral venting boundary conditions and the bias voltage

Abstract: The present paper deals with the analysis of the squeeze film effects in circular capacitive micromachined ultrasound transducers (CMUT) operating in air, with emphasis on improved bandwidth. Firstly, a 1D analytical approach based on parallel plate approximation is recalled. The opposing influences of the electrostatic softening and the squeeze film stiffening make the resonant frequency dependent on the bias voltage with respect to air spring constant to mechanical spring constant ratio. In a second part, FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Due to the pressure difference, air flows from higher-pressure regions to lower-pressure regions in the sealed cavity, which consequently results in viscous loss [41,42]. Galisultanov et al investigated the damping effect in CMUTs and revealed that, for a squeeze number higher than 50, CMUTs possess a damping effect as, at a high squeeze number, the viscous damping force is similar for both sealed and open cavities [41,42]. The data in Table A3 show that the proposed CMUT carries a damping effect for the cavity pressure of as low as 300 Pa as per the findings of References [41,42].…”
Section: Appendix A1 Finite Element Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the pressure difference, air flows from higher-pressure regions to lower-pressure regions in the sealed cavity, which consequently results in viscous loss [41,42]. Galisultanov et al investigated the damping effect in CMUTs and revealed that, for a squeeze number higher than 50, CMUTs possess a damping effect as, at a high squeeze number, the viscous damping force is similar for both sealed and open cavities [41,42]. The data in Table A3 show that the proposed CMUT carries a damping effect for the cavity pressure of as low as 300 Pa as per the findings of References [41,42].…”
Section: Appendix A1 Finite Element Analysismentioning
confidence: 99%
“…Since the CMUT acts like a flexible plate instead of a rigid piston, the nonuniform deflection of the membrane results in nonuniform distribution of pressure within the cavity. Due to the pressure difference, air flows from higher-pressure regions to lower-pressure regions in the sealed cavity, which consequently results in viscous loss [41,42]. Galisultanov et al investigated the damping effect in CMUTs and revealed that, for a squeeze number higher than 50, CMUTs possess a damping effect as, at a high squeeze number, the viscous damping force is similar for both sealed and open cavities [41,42].…”
Section: Appendix A1 Finite Element Analysismentioning
confidence: 99%
“…FDM is coupled with the arclength continuation method to determine how the solution of a system varies with respect to a certain parameter [59]. We consider the following algebraic system: F (X, α) = 0 (40) where α is the continuation parameter and X is the unknown parameter. The idea of this method is to avoid varying the parameter α by parametrizing the variables X and α via a new continuation parameter s, X = X(s) and α = α(s).…”
Section: Frequency Response Analysismentioning
confidence: 99%
“…The static and dynamic behavior is very sensitive to residual stress, initial imperfection and squeeze film damping [36,37,38,39]. Galisultanov et al [40] developed a 1D equivalent system, based on a rigid piston model, and a 2D FEM model using COMSOL. The model demonstrates the competition between the electrostatic softening, caused by the DC voltage, and the squeeze film stiffening due to the gap change.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] They have shown that, in spite of a low signal-to-noise ratio compared to the piezoelectric transducer, the CMUTs are able to detect, for example, acoustic emission events. In our work, the CMUTs of interest have been developed by Galisultanov et al 10 and the technology is presented in the next section. A numerical study to optimize the sensor design is presented.…”
Section: Introductionmentioning
confidence: 99%